PENGARUH KEWENANGAN DAN PENGAMBILAN KEPUTUSAN TERHADAP EFEKTIVITAS MANAJERIAL KEPALA SEKOLAH MENENGAH ATAS DI JAKARTA UTARA - Siti Wahdatun Nuriah (Jurnal Manajemen Pendidikan, 2012)
The study aims to obtain empirical data about the presence or absence of a strong and weak linkage between the independent variable authority and decicion making with the dependent variable managerial effectiveness principle on senior high school North Jakarta. The research method used in this research is survey. The sample is 52 respondents taken by proporsional random sampling. The study was conducted to senior high school principlals in North Jakarta. The result of the study pointed out that: (1) there is a direct and significant influence of Authority with managerial effectiveness, (2) there is a direct and significant influence of decision making with managerial effectiveness and (3) there is a direct and significant influence authority with decision making.